AccR Is a Master Regulator Involved in Carbon Catabolite Repression of the Anaerobic Catabolism of Aromatic Compounds in Azoarcus sp. CIB - Valderrama, J. Andrés (American Society for Biochemistry and Molecular Biology, 2014)
Here we characterized the first known transcriptional regulator that accounts for carbon catabolite repression (CCR) control of the anaerobic catabolism of aromatic compounds in bacteria. The AccR response regulator of Azoarcus sp. CIB controls succinate-responsive CCR of the central pathways for the anaerobic catabolism of aromatics by this strain. Phosphorylation of AccR to AccR-P triggers a monomer-to-dimer transition as well as the ability to bind to the target promoter and causes repression both in vivo and in vitro. Substitution of the Asp(60) phosphorylation target residue of the N-terminal receiver motif of AccR to a phosphomimic Glu residue generates a constitutively active derivative that behaves as a superrepressor of the target genes. AccR-P binds in vitro to a conserved inverted repeat (ATGCA-N(6)-TGCAT) present at two different locations within the P(N) promoter of the bzd genes for anaerobic benzoate degradation. Because the DNA binding-proficient C-terminal domain of AccR is monomeric, we propose an activation mechanism in which phosphorylation of Asp(60) of AccR alleviates interdomain repression mediated by the N-terminal domain. The presence of AccR-like proteins encoded in the genomes of other β-proteobacteria of the Azoarcus/Thauera group further suggests that AccR constitutes a master regulator that controls anaerobic CCR in these bacteria.